PENGARUH ANIME TERHADAP GENERASI MUDA DI DENPASAR-BALI - Ni Made Meila Pratiwi; Ni Wayan Meidariani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
Japanese pop culture has become increasingly popular among youth worldwide, including in Indonesia. One prominent element of this culture is anime. This phenomenon in Bali is visible in fashion, daily language, and interest in Japanese culture. This study analyzes the positive and negative impacts of anime on the behavior and lifestyle of youth in Denpasar, Bali. Using a qualitative descriptive approach, data were collected through interviews and open questionnaires with teenage and adult anime fans. Results show that anime is not only a form of entertainment but is also imitated and adapted in everyday life, influencing fashion, speech, and habits inspired by anime characters. Positive impacts include enhanced creativity, self-expression, enthusiasm for learning, interest in Japanese culture, and the formation of communities and a sense of belonging. Negative impacts include addiction, decreased productivity, tendencies toward social isolation, escapism into fantasy, and negative societal perceptions. The imitation process is selective and adapted to local culture and social context. These findings demonstrate anime’s tangible influence on how youth express themselves and shape their lifestyles in Denpasar.